Jungle Laboratories : Mexican Peasants, National Projects, and the Making of the Pill - Soto Laveaga, Gabriela, 1971- (Book collections on Project MUSE., 2009)
Shows how wild yams, once considered useless, briefly became indispensable to the global pharmaceutical industry (as a source of synthetic steroid hormones) and to the peasants who gathered them.